Anthropometric Features of Body Index in Natives of Qazvin, Iran - Keywan Mortezaee; Fatemeh Sabbaghziarani; Gholamreza Hassanzadeh; Noushin Alaghbandha; Ali Dehbashipour (Negah Institute for Scientific Communication, 2013)
Introduction: The purpose of the present study was to evaluate anthropometric characteristics of weight, sitting & standing height, cormic index and BMI in the adult residents of Qazvin, Iran. Methods: In this cross-sectional study, 300 adult inhabitants aged 18-55 years (180 males and 120 females) of Qazvin, Iran were evaluated. The participants were selected randomly and without any physical deformities or any previous history of trauma. Measurements were performed in an anatomical position. Results: Their mean±SD weight was 72.64±11.03 and 66.53±9.48 kg, mean±SD standing height was 171.41±5.33 and 158.24±5.2 cm, mean±SD sitting height was 90.22±4.04 and 86.24±2.45 cm, mean±SD cormic index was 52.51±2.07 and 54.52±1.57 cm and mean±SD BMI was 24.67±3.2 and 26.57±3.64 in males and females, respectively. Conclusion: The result of the present study showed that the mean dimensions of weight, sitting height and BMI parameters were higher than the most of other accomplished studies.